Lindolfo Collor: o olhar de um brasileiro exilado na Europa sobre o regime nazista - Freitas, Miqueline Ferreira de (2015)
The objective of this dissertation was to analyze two important works of the writer, journalist and political Lindolfo Collor, written during his exile in Europe among the years 1938 to 1941. During this period Lindolfo Collor wrote several articles which were published in the newspaper Diário de Notícias of Rio de Janeiro, on the Hitlerian regime and the initial context of the World War II. Afterwards, these articles were gathered in two books "Europa 1939" (1939) and "Sinais dos Tempos" (1942) sources of this dissertation. We chose the challenge of researching the training, the historical route and the condition in wich Lindolfo Collor was exiled; of identify the political, social and cultural changes of this period; analyzing the perspective of Lindolfo Collor before the changes occurred in Europe; as well, as understanding his memories and representations of the experience he lived.